Skeletal Cryptococcosis: Case Report and Review of the Literature - Lori Wood; Lil Miedzinski (Canadian Journal of Infectious Diseases)
A case of isolated cryptococcal skull infection is presented in a patient with unexplained CD4 lymphopenia and chronic hepatitis B. All cases of this disease reported in the English literature from 1956 to the present are reviewed. The literature suggests that skeletal cryptococcosis is manifested in only 5% to 10% of recognized cases of disseminated cryptococcosis and that isolated skeletal disease without evidence of other tissue involvement is even less common. When isolated bony disease does occur it tends to occur in immunocompromised hosts, particularly those with defects of cell mediated immunity. Any bony site can be involved, most commonly the vertebrae, with the presentation often being a soft tissue swelling and pain in the affected area. Systemic constitutional symptoms occur in a minority of patients. Radiographic investigations are nonspecific and the gold standard of diagnosis remains culture isolation from bone tissue. The most commonly employed therapy for isolated bone disease is amphotericin alone or combined with surgical debridement. The new azoles may have a role in future therapy.